A Man's Blessing or a Woman's Curse? The Family Earnings Gap of Doctors. Issue 3 (July 2016) - Schurer, Stefanie; Kuehnle, Daniel; Scott, Anthony; Cheng, Terence C.
Abstract : We examine the size and determinants of the family earnings gap for Australian general practitioners (GPs). Female GPs with children earn more than 30, 000 less than comparable female GPs without children, while male GPs with children earn more than 45, 000 more than comparable male GPs without children. The main determinants of the family gap are differences in observable characteristics such as working hours, labor‐force attachment, and demographics, and additionally, for men, entrepreneurship and practice size. A fixed‐effects extension of the analysis confirms both the carer effect of children on female GPs and the breadwinner effect of children on male GPs.